Determinants of Mobile Accounting App Adoption by Micro, Small, and Medium Enterprise in Indonesia - Kholid, Muamar Nur; Alvian, Shani; Tumewang, Yunice Karina (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
This study figured out the factors that influence Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to adopt a mobile accounting application as a tool to record business transactions and to prepare financial reports. This research applies the Unified Theory of Acceptance and Use of Technology (UTAUT) with two additional variables, namely perceived risk and perceived trust. Using a combination of purposive, convenience, and snowball sampling techniques, this study distributed questionnaires to MSME owners in Indonesia who know the mobile accounting app. Following that, this study uses the Partial Least Square- Structural Equation Model (PLS-SEM) to analyze the data obtained and to confirm the significance of the causality relationship. Effort expectancy, performance expectancy, social influence, and perceived trust have a significant positive effect on the intention to adopt a mobile accounting app. The study provides knowledge of the factors that influence MSME owners' intentions to choose a mobile accounting app which might help app providers to develop strategies to meet the expectation of MSME owners. This study merely examines the intention to adopt a mobile accounting app, hence further study could examine the user's intention to continue using the mobile accounting app, by using the longitudinal data collection.